Short-Term Influence of Caffeine and Medium-Chain Triglycerides on Ketogenesis: A Controlled Double-Blind Intervention Study - Anna Baumeister; Joachim Gardemann; Manfred Fobker; Verena Spiegler; Tobias Fischer (Journal of Nutrition and Metabolism)
Background. Ketone bodies are a highly relevant topic in nutrition and medicine. The influence of medium-chain triglycerides (MCT) on ketogenesis is well known and has been successfully used in ketogenic diets for many years. Nevertheless, the effects of MCTs and coconut oil on the production of ketone bodies have only partially been investigated. Furthermore, the increased mobilisation of free fatty acids and release of catabolic hormones by caffeine suggest an influence of caffeine on ketogenesis. Methods. In a controlled, double-blind intervention study, seven young healthy subjects received 10 mL of tricaprylin (C8), tricaprin (C10), C8/C10 (50% C8, 50% C10), or coconut oil with or without 150 mg of caffeine, in 250 mL of decaffeinated coffee, over ten interventions. At baseline and after every 40 minutes, for 4 h, ßHB and glucose in capillary blood as well as caffeine in saliva were measured. Furthermore, questionnaires were used to survey sensory properties, side effects, and awareness of hunger and satiety. Results. The interventions with caffeine caused an increase in ßHB levels—in particular, the interventions with C8 highly impacted ketogenesis. The effect decreased with increased chain lengths. All interventions showed a continuous increase in hunger and diminishing satiety. Mild side effects (total = 12) occurred during the interventions. Conclusions. The present study demonstrated an influence of caffeine and MCT on ketogenesis. The addition of caffeine showed an additive effect on the ketogenic potential of MCT and coconut oil. C8 showed the highest ketogenicity.